Influence of bio-inoculant mediated organic nutrient management on productivity and profitability of pigeonpea (Cajanus cajan) in a semi-arid agro-ecology - GUPTA, GAURENDRA; DHAR, SHIVA; DASS, ANCHAL; SHARMA, V K; SINGH, RAMESH K; KUMAR, ADARSH; JINGER, DINESH; KUMAR, AMIT (The Indian Journal of Agricultural Sciences, 2018)
An experiment was conducted at ICAR‒Indian Agricultural Research Institute, New Delhi during kharif season of 2016 and 2017 to study the influence of bio-inoculants (BI) mediated nutrient management on yield attributes, yields and economics of pigeonpea [Cajanus cajan (L.) Millsp.]. Experiment was conducted in randomized block design (RDB) with three replications consisting of nine nutrient management treatments, viz. Control, RDF (30: 60:40 NPK), RDF + Bio-inoculant (BI), Vermicompost-VC (5 t/ha), FYM (5 t/ha), Leaf compost-LC (5 t/ha), VC + BI, FYM + BI and LC + BI. Rhizobium leguminosarum, PSB (Pseudomonas putida, Pseudomonas striata, Bacillus subtilis, Bacillus megaterium) and potassium solubilizers (Bacillus mucilagenosus and Frateuria aurantia) were used as bio-inoculants for seed treatment. Results indicate that BI mediated nutrient management significantly increased the pods/plant. Combined effect of inoculation and organic sources of nutrients was significantly higher while inoculation with RDF remained non-significant over sole organic sources of nutrients as well as RDF. Application of FYM with BI produced highest pods/plant, grains/pod and test weight. Application of FYM with BI produced highest seed (1.6; 1.7 t/ha), stover (6.33; 6.5 t/ha) and biological yields (7.93, 8.22 t/ha) respectively during 1st and 2nd year which was at par with yield under plots applied with vermicompost and BI. Gross returns, net returns and B: C were significantly affected by the treatments. Application of FYM with BI gave higher gross returns, net returns and B: C. Overall, Significantly higher pigeonpea productivity and profitability was achieved with organic nutrient source + BI over their sole application.